Changes in freshwater sediment microbial populations during fermentation of crude glycerol - Paiders, Matiss; Nikolajeva, Vizma; Makarenkova, Galina; Orola, Liana; Dimanta, Ilze; Kleperis, Janis (Pontificia Universidad Catolica de Valparaiso, 2021)
Background: This work studied how the exposure to an unusual substrate forced a change in microbial populations during anaerobic fermentation of crude glycerol, a by-product of biodiesel production, with freshwater sediment used as an inoculum. Results: The microbial associations almost completely (99.9%) utilized the glycerol contained in crude glycerol 6 g L−1 within four days, releasing gases, organic acids (acetic, butyric) and alcohols (ethanol, n-butanol) under anaerobic conditions. In comparison with control medium without glycerol, adding crude glycerol to the medium increased the amount of ethanol and n-butanol production and it was not significantly affected by incubation temperature (28 °C or 37 °C), nor incubation time (4 or 8 d), but it resulted in reduced amount of butyric acid. Higher volume of gas was produced at 37 °C despite the fact that the overall bacterial count was smaller than the one measured at 20 °C. Main microbial phyla of the inoculum were Actinobacteria, Proteobacteria and Firmicutes. During fermentation, significant changes were observed and Firmicutes, especially Clostridium spp., began to dominate, and the number of Actinobacteria and Gammaproteobacteria decreased accordingly. Concentration of Archaea decreased, especially in medium with crude glycerol. These changes were confirmed both by culturing and culture-independent (concentration of 16S rDNA) methods. Conclusions: Crude glycerol led to the adaptation of freshwater sediment microbial populations to this substrate. Changes of microbial community were a result of a community adaptation to a new source of carbon. How to cite: Paiders M, Nikolajeva V, Makarenkova G, et al. Changes in freshwater sediment microbial populations during fermentation of crude glycerol.
This work was supported by the Latvian Council of Science , project NN-CARMA, project No. lzp-2018/1-0194.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Actinobacteria; Anaerobic fermentation; Clostridium; Crude glycerol; Firmicutes; Freshwater sediment microbial populations fermentation; Gammaproteobacteria; Microorganisms; qPCR